High-efficiency adsorption of Cd2+ and Cr3+ by sodium vanadate nanowire arrays - Peng, Dengzeyu; Fan, Xin; Fang, Dong (Frontiers in Materials, 2023)
With the development of economy, the problem of heavy metal pollution in water environment is becoming more and more serious, so it is urgent to find a kind of efficient water purification material. The current work aimed to investigate the potential power of sodium vanadate nanowire arrays (Na5V12O32) to remove cadmium (Cd2+) and chromium (Cr3+) from simulated aqueous solutions. The adsorption effects of Na5V12O32 on Cd2+ and Cr3+ under different adsorption conditions were analyzed. The products before and after adsorption were compared by XRD, SEM, TEM, FTIR and XPS. The results showed that the irregular grass-like structure of Na5V12O32 nanowire arrays provided more active sites for the ion exchange reaction, and the maximum adsorption capacity of Cd2+ and Cr3+ was 541.2 and 251.8 mg·g-1, respectively. The pseudo-second-order kinetic model was more suitable to describe the adsorption behavior by kinetic study. The research demonstrated that Na5V12O32 nanowire arrays exhibited excellent adsorption performance, which provided an effective parameter basis for the future adsorption of heavy metal ions.